The Role of Cyber Media and Public Science Education - Yunita Sari; Siti Nur Sya'adah (Postgraduate, University of Mataram, 2023)
The purpose of this paper is to describe the role of cyber media in educating the public about science. This is very elementary because practical science knowledge will provide construction of knowledge and experience to students and society in general. This research method is descriptive qualitative with a literature study approach. The data sources in this study are journal articles that are compatible with the research theme, other sources are manuscripts, thoughts, videos and others that can be substantially elaborated, so as to produce a complete picture of the theme of the study being discussed. The results of the study found how cyber media made a significant contribution to the science education of the community and students. the role can be detailed, namely it plays a role in cognitive effects, so that practical science can be absorbed by the wider community, in affective effects, cyber media is able to influence mental attitudes when people meet with various empirical realities day by day.Â Cyber media provides a wealth of information about science and technology to the general public. It is a form of technological devotion to humans, to create convenience in celebrating life, which is increasingly complicated in an overflow of unexplainable needs. In the end, this technological dedication provides a real mirror of how the civilization built by humans with the permission of the almighty, is the glory of humans equipped with qualified reason. In the context of this study, the content of cyber media provides three strata of effects, namely cognitive, affective and psychomotor, whose final result is an increasingly complex change in civilization